Exposure to moxifloxacin and cytomegalovirus replication is associated with skin squamous cell carcinoma development in lung transplant recipients. (25th September 2015) - Gerber, S.R.; Seifert, B.; Inci, I.; Serra, A.L.; Kohler, M.; Benden, C.; Hofbauer, G.F.L.; Schuurmans, M.M.
Abstract: Background: Lung transplant recipients (LTR) are at increased risk for squamous cell carcinoma of the skin (SCC), but risk factors (RF) are incompletely understood. Objective: To assess associations between exposure to certain medications and viral infections, and subsequent SCC development. Methods: Retrospective study examining incidence and potential RF for SCC in LTR transplanted from 1992 to 2010 followed up at one centre. Cumulative incidence and Cox proportional hazards regression models were used to evaluate RF in the first year post‐transplant for SCC formation during the follow‐up. Results: In 205 analysed LTR, 46 patients were diagnosed with SCC during a median follow‐up of 4.9 years. The cumulative incidences of first SCC were 16.7% and 34.1%, for 5 and 10 years post‐transplantation respectively. Multivariable analysis identified CMV replication (HR 7.69, 95% CI 2.93–20.2, P < 0.001) and moxifloxacin exposure (HR 2.35, 95% CI 1.15–4.81, P = 0.020) during the first year post‐transplantation as independent RF for SCC development during follow‐up. Conclusion: In our cohort, moxifloxacin use and CMV replication during the first year post‐transplantation were associated with increased risk for SCC. These two factors could be indicators of over‐immunosuppression. Their role in SCC development requires investigations in larger cohorts and prospective studies.